195k views
2 votes
I need the answers for these

I need the answers for these-example-1
User Eclectic
by
4.4k points

1 Answer

7 votes

Answer:

x = 2

Explanation:

Let's solve your equation step-by-step.

4 ( x − 1 ) = 2 ( 6 − 2 x )

Step 1: Simplify both sides of the equation.

4 ( x − 1 ) = 2 ( 6 − 2 x )

( 4 ) ( x ) + ( 4 ) ( − 1 ) = ( 2 ) ( 6 ) + ( 2 ) ( − 2 x ) (Distribute)

4 x + − 4 = 1 2 + − 4 x

4 x − 4 = − 4 x + 12

Step 2: Add 4 x to both sides.

4 x − 4 + 4 x = − 4 x + 12 + 4 x

8 x − 4 = 12

Step 3: Add 4 to both sides.

8 x − 4 + 4 = 12 + 4

8 x = 16

Step 4: Divide both sides by 8.

8 x / 8 = 16 / 8

x = 2

User Webbiedave
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.